Optical coherence tomography-angiography as a non-invasive method of pathology diagnosis of the microcirculatory bed of the optic nerve and macula - M. S. Krivosheeva; E. E. Ioyleva (Российский офтальмологический журнал, 2021)
The review discusses the development of optical coherence tomography with the function of angiography, focusing on its advantages, features, and prospects for the diagnosis of fundus pathologies.